REVITALISASI TAMAN KOTA SIGLI SEBAGAI RUANG PUBLIK YANG BERNUANSA ISLAMI - Desi Safriana (Department of Architecture, Faculty of Engineering, University of Muhammadiyah Aceh, 2021)
The existence of a city park is very important in urban planning. In addition to functioning as a public facility, city parks are also very important if viewed from various aspects. Based on the Aceh Provincial Spatial Plan, each Regency/City must have a Green Open Space (RTH) area of 30%. This research takes place in Sigli City which is one of the sub-districts in Pidie Regency, Aceh Province, Indonesia. The Sigli City Government is currently carrying out developments on varioussides, one of which is the construction of city parks as facilities for green open spaces and public spaces. The City Park,which is located on Jalan Merdeka, precisely on the banks of the Sigli river, has the potential to accommodate the needs ofthe community for the need for open space or public facilities. However, based on the author's observations at the location,this city park looks deserted from visitors, poorly maintained and misused as a garbage dump. This is certainly verydetrimental to the community and the environment, considering that this city park is a public facility that must be optimized properly. To increase visits and utilization of Sigli City Park, action is needed for changes or revitalization. To find out what actions must be taken, it is necessary to identify the perception of the people of Sigli about the park. For this reason, this research was carried out in order to create a representative city center park with Islamic nuances as part of the central public space of Sigli City. Based on the research findings, it has been planned to reorganize Sigli City Park which is representative and has an Islamic nuance. It is hoped that this research can contribute to the Government and the people of Sigli City.